Pengaruh Komik Isi Piringku terhadap Asupan Karbohidrat dan Protein pada Anak Gizi Lebih - Joyeti Darni; Eva Agustina (Poltekkes Kemenkes Mataram, 2020)
Background: Communication, Information and Education (IEC) of nutrition for school children can shape children's eating habits from an early age in order to achieve a better individual situation in the future. Comics are able to display simple stories and writing in colloquial so that they are easy to understand. Research Methods. This is a quasi experimental study with control group pretest-posttest design. Subjects were taken with a simple random sample of 60 students who were divided into two groups, the first group was given education with comic Isi Piringku and the second group was given education without comic Isi Piringku. The carbohydrate and protein intake data in two groups were analyzed using the paired t-test. Research Result. The analysis showed that the highest protein intake enhancement occurred in the treatment group with a delta of 16.7 g, while the control group was 6.2 points. The carbohydrate intake before treatment was 191,9 g and increased after given comic Isi Piringku by 193,4 g. The results of different test showed that there were significant differences in the enhancement of protein intake before and after the provision of nutrition education between the control group and the treatment group with p value <0.05, carbohydrate intake was not significantly different before and after treatment.